2001
DOI: 10.1038/sj.gt.3301551
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient gene transfer into murine liver achieved by intravenous administration of naked Epstein–Barr virus (EBV)-based plasmid vectors

Abstract: Naked plasmid DNA (pDNA) injection could become an alternative procedure to viral and nonviral gene delivery systems. We have previously shown that Epstein-Barr virus (EBV)-based plasmid vectors containing the EBV nuclear antigen 1 (EBNA1) gene and the oriP sequence enable quite high and long-lasting expression in various in [9][10][11] and to a lesser extent, in the spleen, kidney, lung and heart. 9 The expression levels critically depended on the injection volume and rate, strongly suggesting that the 'hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 35 publications
(46 reference statements)
0
38
0
Order By: Relevance
“…The plasmids pGEG.GL3 [28], pGE-G.EGFP [29], and pGEG.b [30] carried GL3 firefly luciferase (Luc), EGFP, and Escherichia coli b-galactosidase (b-gal) genes, respectively, under the control of the CAG promoter. Each plasmid also contained Epstein-Barr virus (EBV) nuclear antigen 1 (EBNA1) gene and EBV oriP sequence [31].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The plasmids pGEG.GL3 [28], pGE-G.EGFP [29], and pGEG.b [30] carried GL3 firefly luciferase (Luc), EGFP, and Escherichia coli b-galactosidase (b-gal) genes, respectively, under the control of the CAG promoter. Each plasmid also contained Epstein-Barr virus (EBV) nuclear antigen 1 (EBNA1) gene and EBV oriP sequence [31].…”
Section: Methodsmentioning
confidence: 99%
“…At the same time as the initiation of the injection, transthoracic ultrasound insonation (sonication) was performed through a 6-mm diameter probe with an input frequency of 1 MHz, an output intensity of 1.0-2.0 W/cm 2 , a pulse duty ratio (PDR) of 10-50%, and a duration of 60 s. A Sonitron 2000 (Rich-Mar, Inola, OK, USA) was used to generate the ultrasound. Hydrodynamics-based transduction was performed as described previously [28]. Briefly, 40 lg siRNA-GFP was diluted in 1600 ll PBS and injected intravenously within 4s via the tail vein using a 27-gauge needle.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that use of an Epstein-Barr virus (EBV)-based plasmid vector that harbors the EBV nuclear antigen 1 (EBNA1) gene and oriP sequence further improved the hydrodynamics-mediated transfection, in terms of the transfer efficiency as well as magnitude and longevity of expression. 5 The herpes simplex viruses cause a variety of clinical illnesses that are painful and often distressing. 6,7 These include oral-facial, genital, ocular, and cutaneous herpes, herpes encephalitis, neonatal herpes, and erythema multiforme.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] As a result, the animals were highly resistant to a subsequent lethal HSV-1 challenge. 13 The surviving mice also escaped latent infection, which was not reported in earlier studies using intramuscular pDNA vaccination.…”
Section: Introductionmentioning
confidence: 99%